A single-dose PLGA encapsulated protective antigen domain 4 nanoformulation protects mice against Bacillus anthracis spore challenge. - Manish Manish (Public Library of Science (PLoS), 2013)
Bacillus anthracis, the etiological agent of anthrax, is a major bioterror agent. Vaccination is the most effective prophylactic measure available against anthrax. Currently available anthrax vaccines have issues of the multiple booster dose requirement, adjuvant-associated side effects and stability. Use of biocompatible and biodegradable nanoparticles to deliver the antigens to immune cells could solve the issues associated with anthrax vaccines. We hypothesized that the delivery of a stable immunogenic domain 4 of protective antigen (PAD4) of Bacillus anthracis encapsulated in a poly (lactide-co-glycolide) (PLGA)--an FDA approved biocompatible and biodegradable material, may alleviate the problems of booster dose, adjuvant toxicity and stability associated with anthrax vaccines. We made a PLGA based protective antigen domain 4 nanoparticle (PAD4-NP) formulation using water/oil/water solvent evaporation method. Nanoparticles were characterized for antigen content, morphology, size, polydispersity and zeta potential. The immune correlates and protective efficacy of the nanoparticle formulation was evaluated in Swiss Webster outbred mice. Mice were immunized with single dose of PAD4-NP or recombinant PAD4. The PAD4-NP elicited a robust IgG response with mixed IgG1 and IgG2a subtypes, whereas the control PAD4 immunized mice elicited low IgG response with predominant IgG1 subtype. The PAD4-NP generated mixed Th1/Th2 response, whereas PAD4 elicited predominantly Th2 response. When we compared the efficacy of this single-dose vaccine nanoformulation PAD4-NP with that of the recombinant PAD4 in providing protective immunity against a lethal challenge with Bacillus anthracis spores, the median survival of PAD4-NP immunized mice was 6 days as compared to 1 day for PAD4 immunized mice (p<0.001). Thus, we demonstrate, for the first time, the possibility of the development of a single-dose and adjuvant-free protective antigen based anthrax vaccine in the form of PAD4-NP. Further work in this direction may produce a better and safer candidate anthrax vaccine.